2020
DOI: 10.1186/s40794-020-0105-9
|View full text |Cite
|
Sign up to set email alerts
|

First sequence of influenza D virus identified in poultry farm bioaerosols in Sarawak, Malaysia

Abstract: In 2018, our team collected aerosols samples from five poultry farms in Malaysia. Influenza D virus was detected in 14% of samples. One sample had an 86.3% identity score similar to NCBI accession number MH785020.1. This is the first molecular sequence of influenza D virus detected in Southeast Asia from a bioaerosol sample. Our findings indicate that further study of role of IDV in poultry is necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 17 publications
0
16
1
Order By: Relevance
“…Susceptibility to experimental infection by IDV has been established in mice, guinea pigs, and ferrets [4, [26][27][28]. Despite the absence of IDV antibodies in U.S. poultry as demonstrated in a small-scale study [25], a recent study showing the evident detection of IDV genome in Asian poultry farms appears to add this species into a growing list of susceptible hosts for IDV [29]. The results of these studies collectively support a theory that IDV utilizes bovines as a primary reservoir and amplification host with periodical spillover to other animal hosts (Figure 1).…”
Section: Epidemiology and Host Range Of Influenza D Virusmentioning
confidence: 99%
“…Susceptibility to experimental infection by IDV has been established in mice, guinea pigs, and ferrets [4, [26][27][28]. Despite the absence of IDV antibodies in U.S. poultry as demonstrated in a small-scale study [25], a recent study showing the evident detection of IDV genome in Asian poultry farms appears to add this species into a growing list of susceptible hosts for IDV [29]. The results of these studies collectively support a theory that IDV utilizes bovines as a primary reservoir and amplification host with periodical spillover to other animal hosts (Figure 1).…”
Section: Epidemiology and Host Range Of Influenza D Virusmentioning
confidence: 99%
“…A serological survey that was performed to determine if small ruminants (sheep and goats) and poultry (chicken and turkey) were potential hosts for IDV showed that 5.2 % ( n =557) of sheep serum samples and 8.8 % ( n =91) of goat serum samples were positive for IDV antibodies, while all tested poultry serum samples, collected from multiple midwestern states of the USA, were negative for IDV antibodies () [18]. In contrast to the poultry data reported in this study, the most recent molecular diagnosis study revealed the presence of IDV genomes in poultry farms in Southeast Asia [29]. Partial sequencing of the M segment of these samples showed that the detected IDV in poultry diverged from bovine IDV strains circulating in North America.…”
Section: Epidemiology Of Idv Worldwidementioning
confidence: 78%
“…Since its discovery in pigs, IDV has been isolated in a number of other animal species including cattle, horses, sheep, goat, and camelids. Most recently, we found evidence of IDV in poultry in Sarawak, Malaysia 4 …”
Section: Figurementioning
confidence: 78%